Estudo teórico e comparação experimental dos escoamentos internos e externos descendentes da película de solução água e brometo de lítio em absorvedores de tubos horizontais e verticais - Andrade, Juanice Helena de (2018)
This work presents a hybrid numerical analytical solution for the simultaneous transfer of heat and mass in horizontal and vertical tube absorbers. The Generalized Integral Transformation Technique is applied to solve the system of partial differential equations of energy and mass diffusion, in permanent regime, in the flow of the descending film formed by the solution above the horizontal duct and inside the vertical duct of the absorbers. The technique allows analytical manipulations of systems of partial differential equations and boundary conditions, even if they are nonlinear, to produce systems of ordinary differential equations for transformed potentials. The numerical results found using the DIVIPAG subroutine of the Microsoft IMSL Powerstation package in Fortran language are compared with results available in the literature obtained using the Mathematica program for the horizontal absorber and with experimental results from the existing experimental setup in CREVER - Center for Technological Innovation in Energy and Refrigeration Revalorization, Universitat Rovira i Virgili, Spain. Experimental data for a test situation are used for the parameterization and establishment of the dimensionless ness used in the problem solved. Numerical-experimental simulation results are used to determine the main practical interest parameters, such as average film temperature, mean concentration, Nusselt number and Sherwood number for experimentally established flow conditions. Final observations are made from the results, presented in tables and graphs, and suggestions will be pointed to the adjustment and improvement of the model.